How to create innovation the ultimate guide to proven strategies and business models for drive innovation and digital transformation - Dieffenbacher, Stefan F.; Hüttinger, Caroline; Zaninelli, Susanne M.; Lines, Douglas; Rein, Andreas (Ascent Audio, 2024)
Bringing together a wealth of experience from sixty-plus distinguished global thought leaders, How to Create Innovation is a comprehensive guide to becoming a leader in innovation and an organization that plays to win, containing all of the working methods, separate business innovation models, and processes you need to transform your organization digitally. Written by Stefan F. Dieffenbacher, founder of an international award-winning consulting agency, the book draws upon Dieffenbacher's experiences working with clients like Amazon, BMW, Google, and Pfizer to deliver a one-stop, end-to-end solution to innovative transformation. In this book, listeners will learn how to uncover opportunities by finding your niche and devising a more nuanced business strategy; lead culture change by recognizing and avoiding common reasons for failure; and harness proven strategies developed under the Understanding and Navigating Innovation and Transformation in Enterprises (UNITE) model. With ready-to-use assets included to help you start taking action immediately, How to Create Innovation earns a well-deserved spot on the bookshelves of business leaders, entrepreneurs, and managers who want to take their organizations to the next level and overcome the competition through tried and tested strategies for innovation.
Online resource; title from title details screen (O'Reilly, viewed August 13, 2024)
Keywords: Business enterprises -- Technological innovations; Technological innovations -- Management; Entreprises; Innovations; Innovations; Gestion; Audiobooks; Livres audio